2018
DOI: 10.3126/jist.v22i2.19602
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Influences of Artemisia Dubia Wall. Ex. Besser on Seed Germination and Seedling Vigor of Parthenium Hysterophorus L

Abstract: Allelopathic effect of aqueous (leachate) and solvent extract (hexane, chloroform, methanol and water) of leaf, stem and root of donor plant Artemisia dubia was studied on germination and seedling vigour of Parthenium hysterophorus. Extraction and quantification of different parts in different solvent was done by percolation method. Bioassay was performed by allowing P. hysterophorus seed to germinate in Petri dishes (for solvent, aqueous) in laboratory condition against varied concentrations of prepared extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Further, all the treatments, especially combined exudates, caused a reduction in root growth (root length and biomass), indicating root inhibition ( Figure 2 ), whereas Bromus sterilis exhibited an increased root growth under all the treatments, which once again suggests the potential hormesis. Other studies also found differential root growth effects of allelopathy contingent upon the invader species [ 78 ]. Varying shoot and root growth responses of Veronica persica and Bromus sterilis reveal the different allelochemical sensitivities of these invasive species.…”
Section: Discussionmentioning
confidence: 98%
“…Further, all the treatments, especially combined exudates, caused a reduction in root growth (root length and biomass), indicating root inhibition ( Figure 2 ), whereas Bromus sterilis exhibited an increased root growth under all the treatments, which once again suggests the potential hormesis. Other studies also found differential root growth effects of allelopathy contingent upon the invader species [ 78 ]. Varying shoot and root growth responses of Veronica persica and Bromus sterilis reveal the different allelochemical sensitivities of these invasive species.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies indicated that these compounds were also present in concentrated extracts of other Artemisia spp. [15] and in different solvent extracts of Artemisia dubia [5,16]. The presence of these secondary metabolites as bioactive components that were identified during the qualitative phytochemical tests may be responsible for the molluscicidal activity of wormwood EE.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activity of plants with allelochemicals depends on the concentration. Characteristic responses include stimulation at low concentrations of allelochemicals but inhibition as concentrations increase [33]. Therefore, it is concluded that its bio-stimulant effect on crops and herbicidal effect on weeds can make it an ideal solution in an integrated crop protection program.…”
Section: Effects Of Aqueous Extracts On Crops and Weedsmentioning
confidence: 99%